The Decline of Contemporary Celtic Paganism in the Czech Republic: Factors in the Growth and Erosion of Czech Celtophilia - Reichstäter, Jan (Pomegranate, 2018)
In the ancient reports that mention the ethnic situation in the present day Czech Republic region, the Celtic tribe of the Boii appears as the first known inhabitants. This information, together with specific political circumstances in the post-war period, has given rise to a cultural trend of modern Czech Celtophilia. This phenomenon, meaning "love of things Celtic" and concerning usually Celtic cultures or peoples (either historical or modern), can be also considered as a basis for modern Celtic Paganism, which seeks to revive and adapt old Celtic religiosity for contemporary use. The following text will address the phenomenon of Celtophilia within the framework of Czech identity and history. The discussion will deal with two main issues: (1) the historical development of Czech Celtophilia, in its both non-religious and religious forms, and (2) the dynamics of its present-day decline. Though the reasons for Czech enthusiasm for Celtic history and identity, as well as skepticism about Czech Celticity, were always diverse and variable, the purpose here will be to arrive at a general explanation of these issues and their contributing factors. This brief study will mainly engage with the most evident aspects of the whole phenomenon.